TiO2 Memristor Modelling with LabVIEW - Şahin, Muhammet Emin; Güler, Hasan (Fırat University, 2017)
The fourth fundamental circuit element-Memristor, was mathematically modelled by Prof. Leon Chua in 1971. After about four decades, researchers at the Hewlett–Packard (HP) laboratories submitted the development of a new basic circuit element that completes the missing link between charge and flux linkage, which was suggested by Chua. Though a physical memristor device was not discovered then, many unique simulation applications are executed to take advantage of memristor feature which is different from other circuit elements by many researchers. In this paper, we use TiO2 memristor model on account of its simplified expressions and the same ideal physical behaviors. Firstly, we obtained the mathematical equations of TiO2 memristor. Then, these equations are created with LabVIEW and results are submitted. Finally, results of this system’s behavior and stability analysis of are submitted.